The fate of statistical isotropy - Hofmann, Ralf (Nature physics, 2013)
The latest data from the Planck satellite have consolidated our understanding of the cosmic microwave background and the early Universe — except for some large-angle anomalies. These effects could be accounted for by invoking SU(2) gauge symmetry for photon propagation.